In-class film-viewing for empathy development in higher education - Lemieux, Amélie (Canadian Review of Art Education, 2017)

Moments de réception en lecture et en spectature : Le cas d’Incendies au CEGEP - Lemieux, Amélie (Revue de recherches en littératie médiatique multimodale, 2016)

Think it through: Fostering aesthetic experiences to raise interest in literature at the high school level - Lemieux, Amélie (Journal of the Canadian Association for Curriculum Studies, 2015)

Approches transactionnelle, subjective, et phénoménologique en didactique de la lecture - Lemieux, Amélie; Lacelle, Nathalie (Myriades, 2016)

Mobilizing subjective processes in the literature classroom - Lemieux, Amélie; Lacelle, Nathalie (Language & literacy Canadien Online Journal, 2016)

Mapping Holistic Learning: An Introductory Guide to Aesthetigrams - White, Boyd; Lemieux, Amélie (Peter Lang, 2017)
Mapping Holistic Learning: An Introductory Guide to Aesthetigrams introduces the concept of aesthetigrams. These are participant-produced visual maps of aesthetic engagement. The map-making strategy was originally developed by one of the authors, Boyd White, to assist him in understanding what his university-level students were experiencing as they interacted with artworks. Such interactions are, after all, private, individualistic, and fleeting. How can a teacher foster student/teacher dialogue that might lead to enhanced engagement, much less do research, without a concrete record of such engagement? Aesthetigrams provide that record. Recently, the strategy has been adapted to other fields of study—the teaching of literature, and philosophy for children, as well as the writing of poetry. Boyd White and Amélie Lemieux are persuaded that the strategy could be expanded into other disciplines. For example, might it not be useful for a teacher to know what a student is feeling and thinking as she struggles with a mathematical concept? Mapping Holistic Learning is divided into three sections. Chapter 1 addresses the theoretical framework that underpins the authors’ research. The second section, Chapters 2 to 5, provides examples of aesthetigram usage within the formal education environment, in art and literature classrooms. The third section, Chapters 6 and 7, introduces two recent experiments in informal settings—one in an adult poetry workshop, the other in a philosophy-for-children workshop. It is not necessary to follow the book in chronological order. Readers are invited to attend to the chapters that most closely address their individual interests.

Mobilizing students’ interpretive resources: A novel take on subjective response in the literature classroom - Lemieux, Amélie; Lacelle, Nathalie (Language and Literacy, 2016)

Reflecting selves: Pre-service teacher identity development explored through material culture - White, B.; Lemieux, Amélie (LEARNing Landscapes, 2015)

4e SÉMINAIRE D’ÉTUDE EN LITTÉRATIE MÉDIATIQUE MULTIMODALE, Montréal, 4 avril 2014 | LMM - Boutin, Jean-Francois; Bégin, Mathieu; Majeau, Claude; Lacelle, Nathalie; Lemieux, Amélie; Godin, Geneviève; St-Pierre, René (2014)

3e SÉMINAIRE D’ÉTUDE EN LITTÉRATIE MÉDIATIQUE MULTIMODALE, Montréal, 6 décembre 2013 | LMM - Mercier, Jean-Pierre; Faucher, Christine; Lemieux, Nathalie; Lemieux, Amélie; Boutin, Jean-Francois; Richard, Moniques; Lacelle, Nathalie; Lemerise, Suzanne; Lieutier, Prune; St-Pierre, René (2013)

Metaphysics of embodied schooling – The school bus symposium: A poetic journey of co-created conference space - McLarnon, M.; Wiebe, S.; Richardson, P.; Balsawer, V,; Binder, M.; Browning, K.; Conrad, D.; Fels, L.; Gouzouasis, P.; Human, A.; Kim, A.; Leggo, C.; et al. (Art Research International: A Transdisciplinary Journal, 2016)